STUDENTS COPING MECHANISM TOWARD STRESS IN WRITING SCIENTIFIC PAPERS AT SARI MULIA MIDWIFERY ACADEMY BANJARMASIN, INDONESIA - Widya Astutik; Aulia Rahmi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Academic roles and responsibilities of students become the cause of stress, but it can be from outside or from inside the students itself. The problem is the students’ incapability towards stress, thus they make an adjustment by coping mechanism. Aims: This study aimed to identify coping mechanisms that have been used by the students toward a stress on in writing scientific papers at Sari Mulia Midwifery Academy Banjarmasin. Methods: This study was a qualitative research with case study approach. The data was collected from three primary sources: 1) Sari Mulia Midwifery Academy’s students who are preparing writing scientific papers, 2) three people who met the study criteria, and 3) nine triangulation persons who are parents, friends, and academic advisor to test the credibility of the data. The data was then processed and analysed through the result of the interview using translation, transcription of data coding organizer, and then conclusion was made based on the data that the writer was obtained. Results: The result showed that students used an adaptive coping mechanism to confront the stressful event like a writing scientific paper with doing some effort to solve the problem. Conclusion: Students get stress when they are preparing for writing scientific papers and students do adaptive coping mechanism. As having social support from their closest persons can do adaptive coping mechanism to face the stress. That is important to the school to pay attention to students’ adaptive coping mechanism in order to improve students’ performance, even under high pressure and stress.